Aktivitas Pupisida Ekstrak Etanol Daun Belimbing Wuluh (Averrhoa bilimbi L.) terhadap Kematian Pupa Aedes aegypti L. - Islami, Suryadi; Hardiansyah, Ridwan; Afriyani; Hafizh, Ahmad Fauzan; Temun, Jedo Muchamad Tias (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to determine the pupicidal activity of ethanol extract from bilimbi ( Averrhoa bilimbi L.) leaves against Ae. aegypti pupal mortality. A true experimental design was employed to evaluate the toxicity of various ethanol extract concentrations against pupae over treatment periods of 24 and 48 hours. Mortality rates were recorded and calculated using the WHO mortality formula, and lethal concentrations (LC50 and LC90) were determined via probit analysis to identify concentrations causing 50% and 90% pupal mortality. The results showed that the ethanol extract exhibited dose-dependent pupicidal activity, with the highest mortality observed at 4% concentration, achieving 97.33% mortality after 48 hours. The LC50 values were 2.378% at 24 hours and 1.425% at 48 hours, indicating an increased effectiveness over time. The findings suggest that the ethanol extract of bilimbi leaves has potential as a natural pupicide, offering an eco-friendly alternative for controlling Ae. aegypti populations. Further studies are needed to optimize formulation and field application for sustainable mosquito vector management.